Quantitative Determination of Marker Compounds and Fingerprint Analysis of the Seeds of Vernonia anthelmintica - Zulipiya Maimaiti; Ablajan Turak; Qing Ling Ma; Geyu Liu; Haji Akbar Aisa (International Journal of Analytical Chemistry)
In traditional Chinese medicine, the seeds of Vernonia anthelmintica (L.) Willd. have been widely used for treatment of cough, skin diseases, diarrhea, fever, schistosomiasis, amoebic dysentery, and gastrointestinal problems, especially in the treatment of vitiligo for thousands of years in China. In this study, an effective, reliable, and accurate high-performance liquid chromatography diode array detector (HPLC-DAD) method was developed for quantitative analysis of 3 marker bioactive compounds and chemical fingerprint of the seeds of V. anthelmintica. Data corresponding to common peak areas and HPLC chromatographic fingerprints were analyzed by exploratory hierarchical cluster analysis (HCA) and principal component analysis (PCA) to extract information of the most significant variables contributing to characterization and classification of the analyzed samples. Based on variety and origin, the high-performance thin layer chromatography (HPTLC) method validated the chemical fingerprint results used to screen the in vitro antioxidant activity of V. anthelmintica. The results show that the developed method has potential application values for the quality consistency evaluation and identification of similar instant V. anthelmintica samples. When considered collectively, this research results provide a scientific basis for the improvement of standardization and specification of V. anthelmintica medicinal materials and provide a pathway for the development and utilization of references for the identification of V. anthelmintica herbs.